Gone dark : a Matthew Redd thriller - Steck, Ryan (Steck, Ryan. Matthew Redd thriller, 2025)
"Matthew Redd doesn't go looking for trouble. But this time, it's found him anyway...and he's not the only one in the crosshairs. Late-summer wildfires are a fact of life in Montana. But as an inferno nears Wellington, Matthew Redd gets the unusual call that a team of smoke jumpers has suddenly gone dark. As head of the county's fledgling search and rescue team, Redd drops into the fire zone and finds way more than he bargained for: a killer has taken out the smoke jumper team along with two civilians, and only a terrified young boy is left as witness. Redd and little Jack narrowly escape the raging fire, and Redd calls in Gavin Kline, now acting director of the FBI, to investigate the bigger forces at play. That afternoon, during one of her last clinic shifts before the birth of her second child, Emily Redd loses a young patient to an overdose. Fed up with yet another loss to the opioid crisis--this one a former schoolmate and a wounded veteran--Emily tracks down and confronts the retired doctor responsible for feeding her patient's deadly addiction. Hours later, when their home is attacked, Redd and Emily wonder which of them kicked a hornet's nest--or if they've both stumbled onto pieces of a much bigger puzzle. As the fire closes in, they follow the connections from a corrupt doctor and a local opioid supplier all the way to a murdered whistleblower for a Big Pharma giant. As Redd's concern for young Jack grows, those who want to silence him forever hunt him down. Redd will do whatever it takes to protect the boy and his family...even if it means he'll have to outrun an inferno and come face-to-face with his greatest fear."